2007
DOI: 10.1210/jc.2007-0581
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Androgen Production in Postmenopausal Women

Abstract: The postmenopausal ovary is hormonally active, contributing significantly to the circulating pool of T. Furthermore, this contribution appears to persist in women as long as 10 yr beyond the menopause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
108
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(131 citation statements)
references
References 22 publications
10
108
0
5
Order By: Relevance
“…Sixty percent of testosterone in premenopausal women originates from ovarian sources, whereas 40% is derived from adrenal precursors. Interestingly, this division changes little with the menopause, with about 50% of testosterone levels continuing to be derived from ovarian sources [53][54][55]. Therefore, processes, diseases and medications that affect ovarian and/or adrenal function may affect testosterone levels in pre-or post-menopausal women and may cause androgen deficiency in women.…”
Section: Effects Of Androgen Deficiency and Testosterone Administratimentioning
confidence: 99%
“…Sixty percent of testosterone in premenopausal women originates from ovarian sources, whereas 40% is derived from adrenal precursors. Interestingly, this division changes little with the menopause, with about 50% of testosterone levels continuing to be derived from ovarian sources [53][54][55]. Therefore, processes, diseases and medications that affect ovarian and/or adrenal function may affect testosterone levels in pre-or post-menopausal women and may cause androgen deficiency in women.…”
Section: Effects Of Androgen Deficiency and Testosterone Administratimentioning
confidence: 99%
“…The ovary is an important source of testosterone and other androgens in postmenopausal women (Fogle et al 2007). Synthesis takes place in the stromal tissue under the stimulus of the gonadotropin luteinizing hormone (LH) (Adashi 1994, Laughlin et al 2000.…”
Section: The Postmenopausal Ovary As Source Of Excessive Testosteronementioning
confidence: 99%
“…Adashi 1994, Sluijmer et al 1998, Laughlin et al 2000, Burger 2002, Jongen et al 2003, Fogle et al 2007) which can be corrected by oophorectomy (Adashi 1994, Sluijmer et al 1998, Laughlin et al 2000, Jongen et al 2003, Fogle et al 2007, Kotsopoulos et al 2012. In a study of BRCA1 and BRCA2 mutation carriers, Kotsopoulos et al (2012) observed a significant decrease in the risk of breast cancer in women who are oophorectomized after menopause than that in women in natural menopause and suggested that the reduction of circulating testosterone levels after oophorectomy might account for its protective effect.…”
Section: :11mentioning
confidence: 99%
“…All androgens in postmenopausal women are suggested to be made locally in peripheral target tissues according to the mechanism of local intracrine formation of steroids. The contribution of ovarian production of circulating androgenic precursors and thus potentially supporting this local intracrine metabolism of steroids is underlined by studies showing serum dehydroepiandrosterone (DHEA); the inactive precursor hormone of androgens is higher in intact compared with oophorectomized women (Labrie et al 2011, Labrie 2015, and several studies reported that the serum levels of androgens between ovarian and peripheral veins were significantly different between early and late menopausal women, suggesting that the production of androgens by the ovaries could persist even 10 years after the onset of menopause, but may subsequently decline (Fogle et al 2007, Maruoka et al 2014. Therefore, the degree and duration to which postmenopausal ovaries remain a viable androgen-producing organ is still controversial and not fully understood.…”
Section: Serum Androgen and Increased Risk Of Developing Endometrial mentioning
confidence: 99%